La crise de l’urbain et la condition moderne dans les romans de Saul Bellow - Timea Lönhardt (Anglophonia)
This paper proposes to study the correspondence that Saul Bellow’s novels establish between the urban crisis and the human condition in the United States of the second half of the twentieth century, which will eventually entail a discussion of the writer’s conception of the modern world in its social, political and intellectual aspects. After defining the place and the role of the city in Bellow’s fictional universe, we will note the influence of the research conducted at the Chicago School of Sociology in the first decades of the twentieth century on Bellow’s view of the modern urban environment. We will then analyze in more detail the Bellovian critique of the urban crisis which is the core of the writer’s "city novel", Dean’s December, and which created a lot of controversy in the highly politicized American letters of the 1980s. We will close this analysis with a discussion of the accusations of "cultural conservatism" that Bellow sustained during the 1970s and 1980s, and we will offer an interpretation of the writer’s resistance to contemporary canons as a modern literary requirement.